Pengaruh Pendekatan Matematika Realistik Terhadap Kemampuan Komunikasi Matematis Siswa - Astriani, Nurullita; Dhana, Muhammad Bayu Al (Universitas PGRI Semarang, 2022)
This study aims to determine the effect of realistic mathematics approach on students' mathematical communication skills. This research is a quasi experimental research. The population in this study were all seventh-grade students of SMP Negeri 1 Pangkalan Susu. The samples in this study were 2 classes, namely class VII-3 which was used as an experimental class and class VII-4 was used as a control class. The instrument used was a test in the form of a description of the material Plan Figure. From testing the hypothesis obtained t count (2,250) t table (2.0003) means that Ho is rejected and Ha is accepted. This shows the influence of realistic mathematics approach on students' mathematical communication skills.